Method for improving bonding strength of coating and alloy
By grinding, polishing and cavitating the light alloy, hydroxyl radicals are generated, the oxide layer and micromorphology of the alloy surface are improved, the problem of corrosion of light alloy materials in high humidity and saline-alkali environments is solved, and the performance of coatings and alloys is significantly improved. The bonding strength and the strength of the alloy matrix.
Patent Information
- Application Number
- CN202411196195.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-29
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-08-29
AI Technical Summary
The prior art has shortcomings in improving the stability of coatings and substrates of light alloy materials, especially in high humidity, saline and alkaline environments, where the materials are prone to corrosion, resulting in material failure and economic losses.
After grinding and polishing the light alloy, liquid is used for cavitation treatment to generate hydroxyl radicals, thereby improving the oxide layer and micromorphology of the alloy surface, and an ultrasonic vibration device is used for cavitation treatment to improve the bonding between the coating and the alloy. strength.
It significantly improves the bonding stability between the coating and the alloy and the strength of the alloy matrix, prolongs the durability of the alloy surface coating, and has the characteristics of simple operation, low cost, and broad industrial applications.
Smart Images

Figure CN119327704A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal material surface treatment, and in particular relates to a method for improving the bonding strength between coating and alloy. Background Art
[0002] Light alloys mainly refer to aluminum, magnesium, titanium and their alloys. They are good in appearance, high in specific strength and low in density (aluminum 2.7g / cm 3 、Magnesium 1.74g / cm 3 、Titanium 4.5g / cm 3 ), easy processing and other characteristics show very promising application prospects in energy conservation, emission reduction and lightweighting. However, light alloys, especially aluminum and magnesium alloys, have high chemical activity and electrode potential, and are very prone to corrosion in high humidity, saline and alkali environments, which will not only lead to material failure, economic losses, and safety hazards, but also aggravate environmental pollution. At present, the most commonly used anti-corrosion methods are surface strengthening, alloying, and surface coating. Among them, coating is the most economical and affordable.
[0003] However, as the service conditions become increasingly complex, the requirements for material properties are becoming more stringent, and the requirements for the stability of the combination of coatings and substrates are becoming more stringent. The existing coating process is solidified, and the preparation technology of the coating is mainly focused on strengthening the performance of the coating itself, and rarely involves research on the coating process. Optimizing the coating process while strengthening the base alloy, and combining it with high-performance coatings can achieve the effect of 1+1>2 on the basis of improving the stability of the combination between the coating and the substrate. Therefore, it is of great significance to explore a method that is low-cost, simple in process, excellent in performance, and green and environmentally friendly to improve the bonding strength of the coating and strengthen the base material. Summary of the invention
[0004] Based on the above technical problems, the present invention provides a method for improving the bonding strength between coatings and alloys, which can effectively improve the bonding stability between coatings and alloys, as well as the strength of the alloy matrix, and significantly improve the durability of the alloy surface coating.
[0005] The specific scheme of the present invention is as follows:
[0006] The present invention provides a method for improving the bonding strength between a coating and an alloy, comprising the following steps:
[0007] S1, grinding and polishing the alloy; S2, immersing the alloy after grinding and polishing in liquid, and performing cavitation treatment on the surface of the alloy; S3, applying a coating on the surface of the alloy after cavitation treatment, and drying and curing;
[0008] In S2, the liquid is capable of generating hydroxyl radicals during cavitation treatment.
[0009] Preferably, in S1, the alloy is a light alloy; more preferably, the alloy is selected from at least one of aluminum alloy, magnesium alloy and titanium alloy.
[0010] Preferably, in S1, the roughness of the alloy surface after grinding and polishing is ≤0.4 μm.
[0011] Preferably, in S2, the liquid is water or an aqueous solution; more preferably, the liquid is an aqueous solution of silicon dioxide.
[0012] Preferably, in S2, the liquid temperature is 10-60°C.
[0013] Preferably, in S2, a cavitation treatment device is used to perform cavitation treatment; the vibration head of the cavitation treatment device is immersed in the liquid, and the height of the vibration head from the alloy surface is 0.5-1.2 mm.
[0014] Preferably, in S2, the cavitation treatment device is an ultrasonic vibration device.
[0015] Preferably, in S2, the cavitation treatment parameters are: ultrasonic vibration amplitude of 50-100 μm, ultrasonic vibration frequency of 20-800 KHz, and cavitation treatment time of 0.1-2 h.
[0016] Preferably, in S3, the alloy surface is subjected to coating treatment within 0-48 hours after the cavitation treatment is completed.
[0017] Preferably, in S3, the coating is a water-based coating or a solvent-based coating.
[0018] Preferably, in S3, the coating method is at least one of brushing, spraying and dipping.
[0019] Preferably, in S3, the coating method is selected from ultrasonic dip coating or high-pressure spray coating.
[0020] The beneficial effects of the present invention are:
[0021] The present invention provides a method for improving the bonding strength between a coating and an alloy. The method has the characteristics of simple operation, safety and reliability, short preparation cycle, good repeatability and low cost. A super-hydrophilic surface can be constructed on the surface of an alloy substrate, thereby improving the permeability of the coating and the bonding strength between the coating and the alloy substrate, and significantly improving the strength of the alloy substrate. The method has very broad industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is a schematic diagram of the operation flow of the present invention.
[0023] Figure 2 This is a schematic diagram of the improved ultrasonic vibration device of the present invention.
[0024] Figure 3This is a diagram showing the surface morphology of AZ31B magnesium alloy before and after cavitation and its corresponding element content changes in Example 1.
[0025] Figure 4 This is a diagram showing the change in surface wettability of AZ31B magnesium alloy before and after cavitation in Example 1.
[0026] Figure 5 This is a graph showing the change in methylene blue content in an aqueous solution of AZ31B magnesium alloy before and after cavitation in Example 1.
[0027] Figure 6 This is a graph showing the change in bonding strength between AZ31B magnesium alloy and coating before and after cavitation in Example 1.
[0028] Figure 7 This is a cross-sectional hardness diagram of AZ31B magnesium alloy before and after cavitation in Example 1.
[0029] Figure 8 This is a diagram showing the surface morphology of the AlSi12 aluminum alloy before and after cavitation and its corresponding element content changes in Example 2.
[0030] Fig. 9 This is a diagram showing the change in wettability of the AlSi12 aluminum alloy surface before and after cavitation in Example 2.
[0031] Fig.10 This is a graph showing the change in bonding strength between AlSi12 aluminum alloy and water-based coating before and after cavitation in Example 2.
[0032] Fig.11 This is the cross-sectional hardness diagram of the AlSi12 aluminum alloy before and after cavitation treatment in Example 2.
[0033] Fig.12 This is a diagram showing the change in surface wettability of AZ31B magnesium alloy before and after cavitation in Example 3.
[0034] Fig.13 This is a graph showing the change in bonding strength between AZ31B magnesium alloy and water-based coating before and after cavitation in Example 3.
[0035] Fig.14 This is the cross-sectional hardness diagram of AZ31B magnesium alloy before and after cavitation treatment in Example 3.
[0036] Fig.15 This is a diagram showing the change in wettability of the Ti27Nb alloy surface before and after cavitation in Example 4.
[0037] Fig.16 It is a comparison chart of the bonding strength between AZ31B magnesium alloy and water-based coating in Example 1 and Example 5.
[0038] Fig.17 This is the curve of contact angle change over time of AZ31B magnesium alloy after cavitation in Example 1. DETAILED DESCRIPTION
[0039] The present invention provides a method for improving the bonding strength between a coating and an alloy, comprising the following steps:
[0040] S1, grinding and polishing the alloy; S2, immersing the alloy after grinding and polishing in liquid, and performing cavitation treatment on the surface of the alloy; S3, applying a coating on the surface of the alloy after cavitation treatment, and drying and curing;
[0041] In S2, the liquid is capable of generating hydroxyl radicals during cavitation treatment.
[0042] Preferably, in S1, the alloy is a light alloy; more preferably, the alloy is selected from at least one of aluminum alloy, magnesium alloy and titanium alloy. The light alloy in the present invention refers to an alloy material with low density and light weight, which is prone to surface oxidation. Common light alloys include: aluminum alloy, magnesium alloy and titanium alloy.
[0043] The present invention performs cavitation treatment on the alloy after grinding and polishing in liquid, which can generate a large number of hydroxyl radicals. As a strong polar group, hydroxyl radicals are easy to combine with hydrogen bonds and promote the formation of an oxide layer of a certain thickness on the alloy surface, thereby improving the microscopic morphology of the substrate surface. In addition, a large number of cavitation bubbles rupture on the alloy substrate surface, which will introduce dislocations on the alloy substrate surface, generate residual compressive stress and work hardening, thereby achieving the effect of strengthening the alloy substrate.
[0044] In addition, cavitation treatment can also change the wettability of the alloy matrix. The surface of the alloy matrix after cavitation treatment becomes hydrophilic. Under this condition, coating the alloy surface can help enhance the bonding strength between the coating and the alloy matrix.
[0045] Preferably, in S2, the liquid temperature is 10-60° C. Experiments show that the cavitation intensity of the liquid is high between 10-60° C. Further increase in the liquid temperature will cause changes in factors such as the viscosity and surface tension of the liquid, thereby affecting the cavitation intensity.
[0046] Preferably, in S2, the cavitation treatment parameters are: ultrasonic vibration amplitude of 50-100 μm, ultrasonic vibration frequency of 20-800 KHz, and cavitation treatment time of 0.1-2 hours. More preferably, the ultrasonic vibration frequency is 20-30 KHz.
[0047] Preferably, in S2, a cavitation treatment device is used for cavitation treatment; the vibration head of the cavitation treatment device is immersed in the liquid, and the height of the vibration head from the alloy surface is 0.5-1.2 mm. More preferably, in S2, the cavitation treatment device is an ultrasonic vibration device.
[0048] The cavitation treatment device of the present invention refers to a device that can induce cavitation, including but not limited to an ultrasonic vibration device. An ultrasonic vibration device is a device that uses ultrasound to cause a large number of tiny bubbles (cavitation nuclei) in a liquid to collapse and close rapidly.
[0049] Preferably, in S3, the alloy surface is subjected to coating treatment within 0-48 hours after the cavitation treatment.
[0050] Preferably, in S3, the coating method is selected from ultrasonic dip coating or high-pressure spray coating.
[0051] The high-pressure spraying described in the present invention is a coating process that uses high-pressure equipment to atomize the coating and spray it onto the surface of the object to be coated; ultrasonic dipping is a coating process that uses high-frequency sound wave energy to break the coating molecules to the nanometer level to increase the bonding between the coating and the substrate.
[0052] The invention helps to further enhance the permeability of the coating through ultrasonic dipping or high-pressure spraying, so as to further improve the bonding strength between the coating and the alloy.
[0053] In order to cooperate with the above method, the present invention also provides an improved ultrasonic vibration device such as Figure 2 The ultrasonic vibration device comprises: a 4-DOF spherical parallel motion mechanism 1, a horn 2, and a rotatable blade 3; the two ends of the horn 2 are respectively connected to the 4-DOF spherical parallel motion mechanism 1 and the rotatable blade 3, and the bottom of the horn 2 is connected to a vibration head 7; the horn 2 is provided with a high-pressure liquid delivery pipe 4.
[0054] Preferably, the rotatable blades 3 are controlled to rotate by a motor, and the control speed is 0-50r / s.
[0055] Preferably, there are holes on the surface of the rotatable blade 3 .
[0056] Preferably, the 4-DOF spherical parallel motion mechanism 1 drives the horn 2 to perform omnidirectional motion, which can realize surface modification and coating of materials of different shapes.
[0057] Preferably, an outlet 5 is provided at the bottom of the high-pressure liquid delivery pipe 4 , and the outlet 5 is located at the lower end surface of the horn 2 .
[0058] Preferably, the vibration head 7 is a hollow structure, made of hard alloy, the upper end face is connected to the outlet 5 of the high-pressure liquid delivery pipe 4, and a narrow flow channel 6 is provided 1-4 mm away from the lower end face; the diameter of the narrow flow channel is 0.3-0.5 mm, and the narrow flow channel outlet is located at the lower end face of the vibration head 7.
[0059] Preferably, the speed of the high-pressure liquid delivery pipe can be controlled within the range of 0-200 m / s.
[0060] The high-pressure liquid delivery pipe, rotatable blades, and amplitude rod of the present invention can be used alone or in combination according to the application scenario. For example, when used as a coating coating device, an amplitude rod can be used for vibration-assisted coating or a high-pressure liquid delivery pipe can be used for spraying.
[0061] The technical solutions of the present invention are described in detail below through specific embodiments. However, it should be clearly stated that these embodiments are for illustration only and are not to be construed as limiting the scope of the present invention.
[0062] Example 1
[0063] A method for improving the bonding strength between a coating and an alloy comprises the following steps:
[0064] S1. Grind and polish the surface of AZ31B magnesium alloy to a final surface roughness of 0.1 μm; clean with anhydrous ethanol and blow dry to remove surface oil and ash;
[0065] S2. The ground and polished AZ31B magnesium alloy was completely immersed in 25°C distilled water, and an ultrasonic vibration device was used to perform cavitation treatment on the AZ31B magnesium alloy. The specific parameters were as follows: the vibration head of the ultrasonic vibration device was immersed in the liquid, the height of the vibration head from the alloy surface was 0.5 mm, the ultrasonic vibration amplitude was 52 μm, the ultrasonic vibration frequency was 20 KHz, and the cavitation treatment time was 0.5 h.
[0066] S3. Use anhydrous ethanol to clean the treated AZ31B magnesium alloy to ensure that the stains on the surface of the sample are completely removed and dried; then within 48 hours after the cavitation treatment, spray the anti-corrosion coating onto the surface of the sample through a high-pressure liquid delivery pipe at a spray speed of 6mm / s; use an oven to heat-cure the sample, the oven temperature is controlled at 60℃, and the drying time is 30min.
[0067] The properties of the AZ31B magnesium alloy before and after cavitation treatment and the AZ31B magnesium alloy obtained by coating with S3 in this embodiment were tested, and the results are as follows:
[0068] 1. Figure 3 The surface morphology of AZ31B magnesium alloy before and after cavitation and its corresponding element content change diagram, where before corresponds to the original surface after grinding and polishing, and after corresponds to the sample surface after cavitation treatment.
[0069] It can be seen that obvious oxidation occurred on the surface of AZ31B magnesium alloy after cavitation treatment.
[0070] 2. Figure 4This is a diagram showing the changes in surface wettability of AZ31B magnesium alloy before and after cavitation, where before corresponds to the sample after grinding and polishing, and after corresponds to the sample after cavitation treatment (tested immediately after cavitation treatment, within 48 hours).
[0071] It can be seen that after cavitation treatment, the wetting angle of the surface of AZ31B magnesium alloy decreased from 85.9° to 4.6°, the wettability was significantly improved, and the surface of the sample was super hydrophilic.
[0072] However, the AZ31B magnesium alloy sample after cavitation treatment was placed for 24 days and continuous contact angle test was performed. The contact angle variation curve with time is shown in Fig.17 shown.
[0073] It can be seen that the wetting angle gradually increases with the increase of the standing time, and when the standing time exceeds 2 days, the surface of the sample is converted from a super-hydrophilic state to a hydrophobic state. After standing for 21 days, the surface wetting angle of the AZ31B magnesium alloy increased to 150.8°, and the wettability was significantly reduced, showing super-hydrophobicity. It can be seen that the surface properties of the AZ31B magnesium alloy after cavitation treatment change when it is placed for a certain period of time, which is not conducive to the combination of the coating. Therefore, the present invention performs S3 coating treatment within 48 hours after cavitation treatment.
[0074] 3. Figure 5 This is a graph showing the change in methylene blue content in aqueous solution of AZ31B magnesium alloy before and after cavitation, where before corresponds to the sample after grinding and polishing, and after corresponds to the sample after cavitation treatment.
[0075] Since hydroxyl radicals are highly reactive and have a short lifespan, they are often measured indirectly by converting them into substances that are easy to detect. There are many unsaturated double bonds in the molecular structure of methylene blue, which has strong reducing properties and is often used as a hydroxyl radical scavenger. When hydroxyl radicals react with it, the color gradually fades.
[0076] In this experiment, methylene blue and deionized water were mixed into a 5 mg / L methylene blue solution of 1000 ml as the medium for ultrasonic cavitation. Based on the Lambert-Beer law, the transmittance of the solution at 664 nm (the maximum absorption wavelength of methylene blue) can be measured by an ultraviolet spectrophotometer after the experiment to determine the hydroxyl radical content. When the transmittance of the solution decreases, it indicates that the number of hydroxyl radicals participating in the reaction increases, that is, the number of hydroxyl radicals generated during the cavitation process increases.
[0077] Depend on Figure 5 It can be seen that the content of methylene blue reagent in the aqueous solution of AZ31B magnesium alloy is significantly reduced. Since methylene blue reacts with hydroxyl radicals to form hydroxymethylene blue, it indirectly proves the generation of hydroxyl radicals during the cavitation process, and the number of hydroxyl radicals increases significantly with the increase of ultrasonic cavitation time.
[0078] 4. Figure 6 The graph of the bonding strength between AZ31B magnesium alloy and coating before and after cavitation, where before corresponds to the sample coated without ultrasonic cavitation treatment (i.e., the sample obtained only after steps S1 and S3), and after corresponds to the AZ31B magnesium alloy coated with coating after S3 cavitation treatment.
[0079] It can be seen that the time and test force for peeling of the water-based paint after cavitation treatment are significantly greater than those without cavitation treatment, that is, the bonding strength between AZ31B magnesium alloy and water-based paint is increased by more than 60%.
[0080] 5. Figure 7 It is the cross-sectional hardness diagram of AZ31B magnesium alloy before and after cavitation, where before corresponds to the cross-sectional hardness of the sample without cavitation treatment, and after corresponds to the cross-sectional hardness of AZ31B magnesium alloy after cavitation treatment.
[0081] It can be seen that the surface hardness of AZ31B magnesium alloy is improved after cavitation treatment, and a hardened layer of about 300 μm is formed.
[0082] Example 2
[0083] A method for improving the bonding strength between a coating and an alloy comprises the following steps:
[0084] S1. Grind and polish the surface of AlSi12 aluminum alloy to a final surface roughness of 0.1 μm; clean with anhydrous ethanol and blow dry to remove surface oil and ash;
[0085] S2, completely immersing the AlSi12 aluminum alloy after grinding and polishing in 25° C. distilled water, and performing cavitation treatment on the AlSi12 aluminum alloy using an ultrasonic vibration device, wherein the specific parameters are the same as those of the cavitation treatment in Example 1;
[0086] S3. Use anhydrous ethanol to clean the treated AlSi12 aluminum alloy to ensure that the stains on the surface of the sample are completely removed and dried; then within 48 hours after the cavitation treatment, spray the anti-corrosion coating onto the surface of the sample through a high-pressure liquid delivery pipe at a spray speed of 6mm / s; use an oven to heat-cure the sample, the oven temperature is controlled at 60℃, and the drying time is 30min.
[0087] The properties of the AlSi12 aluminum alloy before and after cavitation treatment and the AlSi12 aluminum alloy obtained by coating with S3 coating in this embodiment were tested, and the results are as follows:
[0088] 1. Figure 8The figure shows the surface morphology of AlSi12 aluminum alloy before and after cavitation and its corresponding element content changes, where before corresponds to the original surface after grinding and polishing, and after corresponds to the sample surface after cavitation treatment.
[0089] It can be seen that obvious oxidation occurred on the surface of AlSi12 aluminum alloy after cavitation treatment.
[0090] 2. Fig. 9 This is a diagram showing the changes in surface wettability of AlSi12 aluminum alloy before and after cavitation, where before corresponds to the sample after grinding and polishing, and after corresponds to the sample after cavitation treatment (tested immediately after cavitation treatment, within 48 hours).
[0091] It can be seen that after cavitation treatment, the surface angle of AlSi12 aluminum alloy decreased from 66.1° to 9.6°, the wettability was significantly improved, and the surface of the sample was super hydrophilic.
[0092] 3. Fig.10 This is a graph showing the change in bonding strength between AlSi12 aluminum alloy and water-based coating before and after cavitation, where before corresponds to the sample coated without ultrasonic cavitation treatment (i.e., the sample obtained only after steps S1 and S3), and after corresponds to the AlSi12 aluminum alloy coated with coating after S1-S3 cavitation treatment.
[0093] It can be seen that the bonding strength between AlSi12 aluminum alloy and water-based coatings is increased by more than 50%.
[0094] 4. Fig.11 This is the cross-sectional hardness diagram of the AlSi12 aluminum alloy before and after cavitation treatment, where before corresponds to the cross-sectional hardness of the sample without cavitation treatment, and after corresponds to the cross-sectional hardness of the AlSi12 aluminum alloy obtained after cavitation treatment.
[0095] It can be seen that the surface hardness of AlSi12 aluminum alloy is improved after cavitation treatment, and a hardened layer of about 325 μm is formed.
[0096] Example 3
[0097] A method for improving the strength of a coating and an alloy, the difference from Example 1 is that (1) the surface roughness after S1 grinding and polishing is 0.128 μm; (2) the cavitation time S2 is 0.25 h, and the other steps and parameters are the same as those in Example 1.
[0098] The properties of the AZ31B magnesium alloy before and after cavitation treatment and the AZ31B magnesium alloy obtained by coating with S3 in this embodiment were tested, and the results are as follows:
[0099] 1. Fig.12This is a diagram showing the change in wettability of the surface of AZ31B magnesium alloy before and after cavitation, where before corresponds to the sample after grinding and polishing, and after corresponds to the sample after cavitation treatment (detected immediately after cavitation treatment, within 48 hours).
[0100] It can be seen that after cavitation treatment, the surface wetting angle of AZ31B magnesium alloy decreased from 85.9° to 6.6°, the wettability was significantly improved, and the surface of the sample was super hydrophilic.
[0101] 2. Fig.13 The graph of the bonding strength change between AZ31B magnesium alloy and water-based coating before and after cavitation, where before corresponds to the sample coated without ultrasonic cavitation treatment (i.e., the sample obtained only after steps S1 and S3), and after corresponds to the AZ31B magnesium alloy coated with coating after S1-S3 cavitation treatment.
[0102] It can be seen that the time and test force for peeling of the water-based paint after cavitation treatment are significantly greater than those without cavitation treatment, that is, the bonding strength between AZ31B magnesium alloy and water-based paint is increased by more than 34%.
[0103] 3. Fig.14 Figure 2 is the cross-sectional hardness diagram of AZ31B magnesium alloy before and after cavitation treatment, where before corresponds to the cross-sectional hardness of the sample without cavitation treatment, and after corresponds to the cross-sectional hardness of AZ31B magnesium alloy after cavitation treatment.
[0104] It can be seen that the surface hardness of AZ31B magnesium alloy is improved after cavitation treatment, and a hardened layer of about 200 μm is formed.
[0105] Example 4
[0106] A method for improving the bonding strength between a coating and an alloy comprises the following steps:
[0107] S1. The surface of Ti27Nb alloy was ground and polished, and the final surface roughness was 0.133 μm; it was cleaned with anhydrous ethanol and blown dry to remove the surface oil and ash layer;
[0108] S2. The Ti27Nb alloy after grinding and polishing is completely immersed in a 30°C silicon dioxide aqueous solution, and an ultrasonic cavitation device is used to perform cavitation treatment on the Ti27Nb alloy. The specific parameters are: the ultrasonic cavitation device is 1.0 mm high from the alloy surface, the ultrasonic vibration amplitude is 60 μm, the ultrasonic vibration frequency is 28 KHz, and the cavitation treatment time is 0.5 h.
[0109] S3. Use anhydrous ethanol to clean the treated Ti27Nb alloy to ensure that the stains on the surface of the sample are completely removed and dried; then spray the anti-corrosion coating onto the surface of the sample through a high-pressure liquid delivery pipe with a spray speed of 6 mm / s; use an oven to heat-cure the sample, the oven temperature is controlled at 60°C, and the drying time is 30 minutes.
[0110] The properties of the Ti27Nb alloy before and after cavitation treatment and the Ti27Nb alloy obtained by coating with S3 coating in this embodiment were tested, and the results are as follows:
[0111] 1. Fig.15 This is a diagram showing the changes in wettability of the Ti27Nb alloy surface before and after cavitation, where before corresponds to the sample after grinding and polishing, and after corresponds to the sample after cavitation treatment (detected immediately after cavitation treatment, within 48 hours).
[0112] It can be seen that after cavitation treatment, the wetting angle of the Ti27Nb alloy surface decreased from 65.6° to 8.9°, the wettability was significantly improved, and the sample surface had superhydrophilicity.
[0113] Example 5
[0114] A method for improving the bonding strength between a coating and an alloy, which is different from Example 1 only in that step S3 uses a roller brush to evenly brush the surface after ultrasonic cavitation, and then places it in an oven at 60° C. for 30 minutes.
[0115] The bonding strength between the AZ31B magnesium alloy obtained in this embodiment and in Example 1 and the water-based coating is compared, as shown in the comparison diagram. Fig.16 It can be seen that the time and test force for the water-based paint to peel off after high-pressure spraying treatment are significantly greater than those of ordinary coating treatment, that is, high-pressure spraying treatment can significantly improve the bonding strength between AZ31B magnesium alloy and water-based paint.
[0116] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for improving the bonding strength between a coating and an alloy, characterized in that: The steps include: S1, grinding and polishing the alloy; S2, immersing the alloy after grinding and polishing in liquid, and performing cavitation treatment on the surface of the alloy; S3, applying a coating on the surface of the alloy after cavitation treatment, and drying and curing; In S2, the liquid is capable of generating hydroxyl radicals during cavitation treatment.
2. The method for improving the bonding strength between coating and alloy according to claim 1, characterized in that: The alloy is a light alloy; preferably, the alloy is selected from at least one of aluminum alloy, magnesium alloy and titanium alloy.
3. The method for improving the bonding strength between coating and alloy according to claim 1 or 2, characterized in that: In S1, the roughness of the alloy surface after grinding and polishing is ≤0.4 μm.
4. The method for improving the bonding strength between coating and alloy according to claim 1 or 2, characterized in that: In S2, the liquid is water or an aqueous solution; preferably, the liquid is a silicon dioxide aqueous solution.
5. The method for improving the bonding strength between coating and alloy according to claim 1 or 2, characterized in that: In S2, the liquid temperature is 10-60°C.
6. The method for improving the bonding strength between coating and alloy according to claim 1 or 2, characterized in that: In S2, a cavitation treatment device is used to perform cavitation treatment; the vibration head of the cavitation treatment device is immersed in the liquid, and the height of the vibration head from the alloy surface is 0.5-1.2 mm.
7. The method for improving the bonding strength between coating and alloy according to claim 6, characterized in that: In S2, the cavitation treatment device is an ultrasonic vibration device.
8. The method for improving the bonding strength between coating and alloy according to claim 1 or 2, characterized in that: In S2, the cavitation treatment parameters are: ultrasonic vibration amplitude is 50-100 μm, ultrasonic vibration frequency is 20-800 KHz, and cavitation treatment time is 0.1-2 h.
9. The method for improving the bonding strength between coating and alloy according to claim 1 or 2, characterized in that: In S3, the alloy surface is subjected to coating treatment within 0-48 hours after the cavitation treatment is completed.
10. The method for improving the bonding strength between coating and alloy according to claim 1 or 2, characterized in that: In S3, the coating method is at least one of brushing, spraying, and dipping; preferably, the coating method is selected from ultrasonic dipping or high-pressure spraying.
Citation Information
Patent Citations
Method of metal performance improvement and protection against degradation and suppression thereof by ultrasonic impact
CN101558174A
Method for increasing coating binding force based on ultrasonic impact
CN109371397A
Ultrasonic-assisted cavitation abrasive grain flow finishing method for titanium alloy surface oxide layers
CN110948398A
Metal with microporous structure on surface as well as preparation method and application of metal
CN114606499A
Cavitation size measuring device, has quartz crystal, regeneration circuit and cable comprising coating removably formed by ultrasound and electrical controller for detecting natural frequency of crystal, regeneration circuit and cable
DE102007028612A1